Better Students Ask More Questions.
Q. If `z=x+iy` satisfies the equation `arg(z-2) = arg(2z+3i)` then `3x-4y` is equal...
1 Answer | add yours
The complex number z = x + i*y. It is given that arg(z - 2) = arg(2z + 3i).
arg(z - 2) = `tan^-1(y/(x-2))`
arg(2z + 3i) = `tan^-1((2y+3)/(2x))`
`tan^-1(y/(x-2))` = `tan^-1((2y+3)/(2x))`
=> `y/(x - 2) = (2y + 3)/(2x)`
=> 2xy = (2y+3)(x-2)
=> 2xy = 2xy+3x-4y-6
=> 3x - 4y = 6
The correct answer is option C.
Posted by justaguide on August 21, 2013 at 6:43 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.